Fat‐to‐muscle ratio as a predictor of insulin resistance and metabolic syndrome in Korean adults. Issue 3 (7th February 2020) - Seo, Young‐Gyun; Song, Hong Ji; Song, Young Rim
Abstract: Background: The present study evaluated the associations of the fat‐to‐muscle ratio (FMR) with metabolic syndrome (MetS) and insulin resistance (IR) in Korean adults using nationally representative survey data. Methods: A two‐stage stratified sampling method was reflected in a cross‐sectional study involving a total of 13 032 participants aged ≥ 19 years who participated in the fourth and fifth Korea National Health and Nutrition Examination Surveys. The homeostasis model assessment for IR (HOMA‐IR) was used to evaluate IR and was calculated as follows: [fasting plasma glucose level (mg/dL) × fasting plasma insulin level (uIU/mL)]/405. MetS was defined using the 2006 International Diabetes Federation criteria, and FMR was measured using whole‐body dual‐energy X‐ray absorptiometry and calculated as follows: total fat mass (kg) divided by total lean mass (kg). In addition, the optimal FMR cut‐off values for detecting MetS and the odds ratios (ORs) for MetS risk were determined according to the FMR quartile and sex. Results: Among all participants, the proportion of women was 58.4%, and the mean age was 44.22 ± 0.26 years. The FMR significantly differed between men and women (0.30 ± 0.002 vs. 0.53 ± 0.003, respectively, P  < 0.001), and the prevalence of MetS and IR gradually increased as FMR increased ( P for trend: <0.001). The optimal FMR cut‐off value for detecting MetS was higher in women than in men (0.555 vs. 0.336, respectively). The negative predictive value was the highest in normal‐weight participants (0.9992 in women and 0.9986 in men), while the positive predictive value was the highest in obese participants (0.5994 in women and 0.5428 in men). Based on the derived cut‐off FMR, a high FMR was associated with poor outcomes in terms of cardiometabolic risk markers ( P  < 0.001). The multivariable‐adjusted ORs for MetS, abdominal obesity, and IR (HOMA‐IR ≥ 3) were 5.35 [95% confidence interval (CI): 4.39–6.52], 7.67 (95% CI: 6.33–9.30), and 3.25 (95% CI: 2.70–3.92), respectively, in men and 5.59 (95% CI: 4.66–6.72), 7.48 (95% CI: 6.35–8.82), and 2.55 (95% CI: 2.17–3.00), respectively, in women. Conclusions: In the present study, a high FMR was significantly associated with the prevalence of MetS and IR. The present findings also showed that FMR can be a novel indicator for detecting the absence or presence of MetS, particularly in metabolically healthy normal‐weight individuals and metabolically obese obese‐weight individuals.